2012
DOI: 10.1016/j.jcrc.2011.10.003
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of short-term mortality in patients undergoing percutaneous dilatational tracheostomy

Abstract: Purpose The purpose of the study was to identify the predictors of short-term mortality in patients undergoing percutaneous dilatational tracheostomy (PDT). Materials and Methods Retrospective analysis of data pertaining to adult patients who underwent PDT between July 2005 and June 2008 in an urban, academic, tertiary care medical center was done. Clinical and demographic data were analyzed for 483 patients undergoing PDT via multivariate logistic regression. Results Mortality data were examined at in-hos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 27 publications
1
7
0
2
Order By: Relevance
“…3,14,16,24,25 The low mortality rate may be attributed to an intensivist model of care delivery for all critically ill patients at the study facility, especially because the SAPS and Acute Physiology, Age, Chronic Health Evaluation scores indicate a high severity of illness and associated increased mortality risk. 3,14,16,24,25 The low mortality rate may be attributed to an intensivist model of care delivery for all critically ill patients at the study facility, especially because the SAPS and Acute Physiology, Age, Chronic Health Evaluation scores indicate a high severity of illness and associated increased mortality risk.…”
Section: Mortality and Hospital Dispositionmentioning
confidence: 99%
“…3,14,16,24,25 The low mortality rate may be attributed to an intensivist model of care delivery for all critically ill patients at the study facility, especially because the SAPS and Acute Physiology, Age, Chronic Health Evaluation scores indicate a high severity of illness and associated increased mortality risk. 3,14,16,24,25 The low mortality rate may be attributed to an intensivist model of care delivery for all critically ill patients at the study facility, especially because the SAPS and Acute Physiology, Age, Chronic Health Evaluation scores indicate a high severity of illness and associated increased mortality risk.…”
Section: Mortality and Hospital Dispositionmentioning
confidence: 99%
“…Although percutaneous dilatational tracheostomy has become a routine procedure for airway management in critically ill patients, this operation is associated with serious complications no less than conventional tracheostomy. 18,19 We believe that both techniques require further improvement.…”
Section: Discussionmentioning
confidence: 99%
“…This is probably because these patients were too sick to even qualify for a tracheostomy. A chart review of 483 patients revealed that patients who received a tracheostomy had a mortality rate of 11% at 2 weeks, 19% at one-month, and 40% at 6 months after tracheostomy [33]. Moreover, in-hospital mortality was found to be 30% in all patients who received a tracheostomy.…”
Section: Mortalitymentioning
confidence: 99%